miR-221-3p Drives the Shift of M2-Macrophages to a Pro-Inflammatory Function by Suppressing JAK3/STAT3 Activation - Quero, Lilian; Tiaden, André N.; Hanser, Edveena; Roux, Julien; Laski, Artur; Hall, Jonathan; Kyburz, Diego (Frontiers in Immunology, 2020)
Abstract Objectives: Macrophages are conventionally classified as pro-inflammatory (M1) and anti-inflammatory (M2) functional types. There is evidence for a predominance of macrophages with an inflammatory phenotype (M1) in the rheumatoid arthritis (RA) synovium. MicroRNAs (miRs) play a pivotal role in regulating the inflammatory response in innate immune cells and are found at dysregulated levels in RA patients. Here we explored miRs that tune the inflammatory function of M2-macrophages. Methods: Expression profiles of miR-221-3p and miR-155-5p were analyzed in clinical samples from RA, other inflammatory arthritis (OIA), osteoarthritis (OA) and healthy donors (HD) by qPCR. In vitro generated macrophages were transfected with miR-mimics and inhibitors. Transcriptome profiling through RNA-sequencing was performed on M2-macrophages overexpressing miR-221-3p mimic with or without LPS treatment. Secretion of IL-6, IL-10, IL-12, IL-8 and CXCL13 was measured in M1- and M2-macrophages upon TLR2/TLR3/TLR4-stimulation using ELISA. Inflammatory pathways including NF-κB, IRF3, MAPKs and JAK3/STAT3 were evaluated by immunoblotting. Direct target interaction of miR-221-3p and predicted target sites in 3’UTR of JAK3 were examined by luciferase reporter gene assay. Results: miR-221-3p in synovial tissue and fluid was increased in RA versus OA or OIA. Endogenous expression levels of miR-221-3p and miR-155-5p were higher in M1- than M2-macrophages derived from RA patients or HD. TLR4-stimulation of M1- and M2-macrophages resulted in downregulation of miR-221-3p, but upregulation of miR-155-5p. M2-macrophages transfected with miR-221-3p mimics secreted less IL-10 and CXCL13 but more IL-6 and IL-8, exhibited downregulation of JAK3 protein and decreased pSTAT3 activation. JAK3 was identified as new direct target of miR-221-3p in macrophages. Co-transfection of miR-221-3p/miR-155-5p mimics in M2-macrophages increased M1-specific IL-12 secretion. Conclusions: miR-221-3p acts as a regulator of TLR4-induced inflammatory M2-macrophage function by directly targeting JAK3. Dysregulated miR-221-3p expression, as seen in synovium of RA patients, leads to a diminished anti-inflammatory response and drives M2-macrophages to exhibit a M1-cytokine profile.